2003
DOI: 10.1248/bpb.26.722
|View full text |Cite
|
Sign up to set email alerts
|

Antipruritic Effects of Sophora flavescens on Acute and Chronic Itch-Related Responses in Mice

Abstract: Pruritus is a dominant symptom of many dermatologic disorders (e.g., atopic dermatitis, contact dermatitis and urticaria), and is a frequent manifestation of several systemic diseases (e.g., chronic renal failure and cholestasis). Antihistaminic and anti-allergic drugs are generally prescribed for cutaneous pruritus. However, histamine is not considered to be the major pruritogen in atopic dermatitis, [1][2][3] because histamine H 1 receptor antagonists do not generally depress itch and scratch in patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In human keratinocytes, an extract inhibited proinflammatory chemokines [60]. A Sophora flavescens extract showed antipruritic effects in a mouse model [61], and in a contact dermatitis mouse model, the topical application of a Sophora flavescens extract reduced hyperplasia, edema, spongiosis, and infiltration of mononuclear cells [51]. …”
Section: Discussionmentioning
confidence: 99%
“…In human keratinocytes, an extract inhibited proinflammatory chemokines [60]. A Sophora flavescens extract showed antipruritic effects in a mouse model [61], and in a contact dermatitis mouse model, the topical application of a Sophora flavescens extract reduced hyperplasia, edema, spongiosis, and infiltration of mononuclear cells [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Our latest research has concentrated on another Chinese herbal medicine, Sophorae Flavescentis Radix (SFR) [12], which has been used in the treatment of viral hepatitis, cancer, enteritis, viral myocarditis, arrhythmia, and skin diseases in China, Japan and some European countries [13][14][15]. Since SFR has specific therapeutic effects on pruritus and allergic symptoms with less side effects [16,17], it has become an important candidate for researchers in studying antipruritic drugs. It has been reported that SFR inhibits histamine signaling, including the decrease of mRNA levels of both histamine H1 receptor (H1R) and histidine decarboxylase (HDC), as well as the reduction of H1R and HDC activities and histamine content, which may contribute to its allergic effects [18,19].…”
Section: Short Communicationmentioning
confidence: 99%
“…al., 2011. It has been proved owning various bioactivities, such as anti-inflammatory, antioxidant, antiarthritic, antimicrobial, cure myocardial fibrosis, neuroprotection, antipruritic, antiandrogen, and protecting chronic heart failure (Yamaguchi-Miyamoto et al, 2003;Cui et al, 2011;Gou et al, 2011;Hu et al, 2011;Jin et al, 2010;Kuroyanagi et al, 1999;Shen et al, 2011). Compared to the cells without oxymatrine pre-treatment, oxymatrine can inhibit ducthe G (2) and M phase of H4IIE (Ho et al, 2009;Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%